Antioxidant activity of Zingiber cassumunar rhizome, Guazuma ulmifolia leaves and their combination in high-fat diet-fed rats - Othman, Fezah; Nurkhasanah Mahfudh, .; Nanik Sulistyani, .; Ika Dyah Kumalasari, .; Randa Sandira Reski, .; Rizal Mahendra, .; Rista Eka Nabila, .; Zakaria, Zainul Amiruddin (Universitas Gadjah Mada, 2024)
Oxidative stress is related to several metabolic diseases, including hyperlipidemia. Previous studies have shown the antioxidant properties of Zingiber cassumunar rhizomes and Guazuma ulmifolia leaves. The objective of this study was to see the antioxidant activity of Z. cassumunar rhizomes, G. ulmifolia leaves extracts, and their combinations in high-fat diet fed (HFD) rat. The water extract of Z. cassumunar rhizomes and G. ulmifolia leaves was evaporated in a freeze dryer to produce dry extracts. The Wistar rats were assigned into six groups at random: normal, positive, negative, Z. cassumunar rhizome extract at 400 mg/kg BW (ZC); G. ulmifolia leaf extract at 50 mg/kg BW (GU), and the combination of Z. cassumunar rhizome extract and G. ulmifolia leaf extract at (350+50) mg/kg BW (ZC+GU). The rats were fed HFD for 28 days, and the treatment groups also received the extracts for the last 14 days. The combination ZC+GU increased the endogenous antioxidant activity namely superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px). The metabolite oxidation, malondialdehyde (MDA) was also found to decrease. The conclusion of the study showed that ZC, GU, and ZC+GU had quite high antioxidant activity to inhibiting oxidative stress.